The Effect of EAP on Job Performance Based on Psychological Contract and Perceived Organizational Support - Cai, Yinquan; Yii, Josephine Ling Chen; Pathak, Shubham (Ital Publication, 2024)
In order to study whether employee assistance programs have a significant impact on job performance, whether psychological contract and perceived organizational support play a mediating role in job performance, and thus provide practical operational strategies for relevant enterprises to propose human resource management suggestions to promote job performance, the implementation of employee assistance programs has been the subject of practical research. The findings indicate that addressing issues related to high turnover, job burnout, and absences cannot be separated from the importance of the psychological contract, perceived organizational support, and employee performance in organizational change. By applying structural equation modeling (SEM) to the data from front-line employees of several units in China, this research tested the relationships among employee assistance programs, psychological contracts, perceived organizational support, and job performance using SPSS and AMOS. The results indicate that employee assistance programs positively affect job performance; psychological contracts and perceived organizational support play a mediating role between employee assistance programs and employee job performance (JOP). Our research suggests that an employee assistance program can optimize frontline employee assistance work, build a mechanism to stimulate frontline employees' psychological contracts, and create an organizational environment full of perceived organizational support. This study innovatively uses the structural equation model for quantitative research. In addition, most previous studies on EPA were based on a single variable, psychological contract, and POS were used as the main intermediary variables to explore the mechanism of their impact on job performance so as to enhance the explanatory power of employee job performance. Doi: 10.28991/ESJ-2024-08-05-018 Full Text: PDF